Effect of Fermented Napier Grass Mixed with Acid Fermented Milk Diet on Nile Tilapia in Cage Culture - Tanakorn Haemasaton; Nithinun Mungmee (My University, 2021)
Aquatic animal feed is a key to the growth of aquatic animals, and the raw materials affect production costs. The use of fermented Napier grass mixed with acid fermented milk for Nile tilapia (Oreochromis niloticus). After it was found that the weights of the fishes were increased. ,the daily weight gain and specific growth rates were significantly different (p < 0.05). Among treatments the fish fed with the fermented napier grass at the level of 10 percent had the highest body weight of 55.12 ± 3.90 grams. The survival rates and feed conversion rate were non-significantly different (p > 0.05). Therefore, it could be concluded that the acid fermented milk diet mixed with fermented napier grass at the level of 10 percent could be used for producing the feeds for Nile tilapia.
Keywords: Nile tilapia; Aquatic life and conservation